MicroRNA-103 represses hepatic de novo lipogenesis and alleviates NAFLD via targeting FASN and SCD1 - Zhang, Meiyuan; Tang, Yan; Tang, E.; Lu, Weirong (Biochemical and biophysical research communications, 2020)
MicroRNAs are well acknowledged as key mediators in the development of chronic metabolic diseases, including NAFLD. However, their roles in hepatic lipid metabolism and fatty liver still remain well elucidated. Here, we found that miR-103 represses de novo lipogenesis (DNL) and dampens the development of obesity/diet-induced fatty liver through targeting at Fasn and Scd1 in mouse liver. miR-103, robustly amplified in obese livers, inhibits the expression of Fasn and Scd1 via directly interacting with their mRNA 3’ untranslated regions. Upregulated miR-103 sufficiently reduces the expression of Fasn and Scd1 and blocks the lipid accumulation in oleate-incubated hepatocytes. Furthermore, specifically overexpressing miR-103 in mouse liver by adenovirus significantly inhibits hepatic DNL to repress HCD-promoted hepatic lipid contents as well as NAFLD development. Meanwhile, enforced expression of hepatic miR-103 also alleviates obesity-associated fatty liver via reducing Fasn and Scd1 in db/db mice. Together, our study reveals a critical role of miR-103 in lipid homeostasis of liver and pathogenesis of NAFLD. •miR-103 inhibits the expression of Fasn and Scd1 via binding mRNA 3′-UTR.•miR-103 blocks the lipid accumulation in oleate-incubated hepatocytes.•Overexpressing miR-103 repress HCD-promoted hepatic lipid contents and NAFLD.•miR-103 overexpression alleviates obesity-associated fatty liver in db/db mice.